Validating THz time-domain spectroscopy as a tool for characterizing low pressure inductively coupled plasmas of ion thrusters - Bräumer, Kalle; Sandoval Rodriguez, Rodrigo; Stein, Markus; Keil, Konstantin; Holste, Kristof; Becker, Felix; Zorn, Jana; Wehkamp, Konrad; Chatterjee, Sangam; Klar, Peter J.; Justus Liebig University Giessen (My University, 2025)
Accurate characterization of plasmas within the discharge chambers of gridded ion engines is essential for their advancement. This study showcases the effectivity of terahertz time-domain spectroscopy (THz-TDS) as a non-invasive technique for profiling low-pressure inductively coupled plasmas, mimicking the conditions of the discharge chamber in a radio-frequency ion thruster. Operating at pressures of 3 - 7 · 10−3 mbar inside the discharge chamber and a supply power of the radio frequency generator ranging from 10 - 80 W, THz-TDS reveals electron densities in the range of 2 · 1016 - 2 · 1017 m−3 for xenon, krypton, and argon plasmas. Our results show good agreement with Langmuir probe measurements and global plasma modeling, highlighting the accuracy and reliability of THz-TDS. This validation, conducted under conditions representative of gridded ion engines, demonstrates that THz-TDS is, in principle, suitable for characterizing the electron system of the plasma ignited in such thrusters in operation. This offers great potential of developing a promising additional tool for plasma diagnostics in electric propulsion systems.
Keywords: ddc:530